Differential expression of androgen, estrogen, and progesterone receptors in benign prostatic hyperplasia - Song, Lingmin (Bosn J Basic Med Sci, 2016)
This study aimed to identify the differential expression levels of androgen receptor (AR), estrogen receptors (ERα, ERβ), and progesterone receptor (PGR) between normal prostate and benign prostatic hyperplasia (BPH). The combination of immunohistochemistry, quantitative real-time reverse transcription polymerase chain reaction, and Western blotting assay was used to identify the distribution and differential expression of these receptors at the immunoactive biomarker, transcriptional, and protein levels between 5 normal human prostate tissues and 40 BPH tissues. The results were then validated in a rat model of BPH induced by testosterone propionate and estradiol benzoate. In both human and rat prostate tissues, AR was localized mainly to epithelial and stromal cell nuclei; ERα was distributed mainly to stromal cells, but not exclusively; ERβ was interspersed in the basal layer of epithelium, but sporadically in epithelial and stromal cells; PGR was expressed abundantly in cytoplasm of epithelial and stromal cells. There were decreased expression of ERα and increased expression of PGR, but no difference in the expression of ERβ in the BPH compared to the normal prostate of both human and rat. Increased expression of AR in the BPH compared to the normal prostate of human was observed, however, the expression of AR in the rat prostate tissue was decreased. This study identified the activation of AR and PGR and repression of ERα in BPH, which indicate a promoting role of AR and PGR and an inhibitory role of ERα in the pathogenesis of BPH.